Iranian Youth and the Hallyu Phenomenon: A Study of Media Influence and Cultural Affinity - Fathi, Elham; Ebrahimi Varzaneh, Leila (Shahroud Journal of Medical Sciences, 2025)
Background: The Hallyu phenomenon—referring to the global diffusion of South Korean popular culture—has expanded rapidly in both reach and influence, particularly among adolescents. This trend holds specific relevance in Iran, where youth engagement with foreign media intersects with cultural identity formation and sociopolitical sensitivities surrounding globalized content. Accordingly, this study explores how Iranian female adolescents and young adults engage with Hallyu and develop loyalty toward South Korean entertainment. Methods: This qualitative study utilized conventional content analysis following the approach of Graneheim and Lundman, suitable for exploring emerging, context-dependent social phenomena. Eleven female participants aged 13 to 22, residing in Tehran and identified as active fans of South Korean popular culture, were selected through purposive sampling. Semi-structured interviews, each lasting between 45 to 120 minutes, were conducted. Data collection continued until data saturation was achieved, meaning no new themes or insights emerged. Results: Analysis yielded three main themes and seven sub-themes: (1) Initial exposure pathways to Hallyu content, (2) Attraction mechanisms through symbolic representation, aesthetic appeal, and linguistic features, and (3) Construction of group identity and deep-seated loyalty to the Hallyu phenomenon. These findings suggest that Hallyu functions not only as entertainment but as a meaningful medium through which Iranian youth negotiate identity, belonging, and cultural expression. Conclusions: The study contributes to the understanding of transnational media influence by highlighting how Iranian youth adopt and adapt global cultural products. The findings offer implications for researchers, educators, and policymakers concerned with media globalization, adolescent identity, and sociocultural transformation in non-Western contexts.